IMPLEMENTASI PENGGUNAAN KOLASE DALAM MENINGKATKAN MOTORIK HALUS ANAK USIA DINI: Kolase - Khoirun Nisa (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2021)
The teaching and learning process is a process that contains a series of actions by teachers and students on the basis of reciprocal relationships that take place in educational situations to achieve certain goals. Early Childhood Learning has a different way from adult learning such as: playing while learning, learning that is fun and interesting for children. fine motor development of learners should also increase at the age of four to five years. The coordination of eyes and hands is getting better, students can use fine motor skills with the help of adults such as: drawing, coloring, sticking, matching, writing, folding, and so on. In fine motoric development, the learning process that occurs is more about coloring activities. The activity of using natural collage materials will make students interested and excited in participating in learning and the fine motor skills of children will increase.